Transient Stability Enhancement of Wind Generator by PWM Voltage Source Converter and Chopper Controlled SMES Unit - Sheikh, M. R. I.; Nasiruzzaman, A. B. M. (Journal of Scientific Research, 2009)
In order to investigate the impacts of the integration of wind farms into utility networks, transient stability should be analyzed before connecting wind turbine generator system (WTGS) to the power system. This paper proposes a robust controller for Superconducting Magnetic Energy Storage (SMES) unit to enhance the transient stability of a grid connected fixed speed wind generator system. In the proposed controller, both SMES active and reactive powers are controlled to decrease the fluctuations of output power and terminal voltage of the wind generator during transient condition. The power conversion system (PCS) of SMES unit used in this paper is composed of a sinusoidal Pulse Width Modulated Voltage Source Converter (PWM-VSC) and a two-quadrant DC-DC chopper using Insulated Gate turn-off Bipolar Transistors (IGBT). Stability during symmetrical and unsymmetrical faults in the network system is analyzed. The effects of the faults on the generator dynamics are also discussed clearly. Simulation results demonstrate that the proposed SMES controller is very effective for stabilizing wind generator as well as the entire power system. Keywords: Fixed speed wind generator system; Transient analysis; System faults; PWM-VSC; DC-DC chopper and SMES unit. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i2.2281